Rediscovering, Reevaluating, and Restoring Lost River-Wetland Corridors - Wohl, Ellen; Castro, Janine; Cluer, Brian; Merritts, Dorothy; Powers, Paul; Staab, Brian; Thorne, Colin (Frontiers in Earth Science, 2021)
River-wetland corridors form where a high degree of connectivity between the surface (rheic) and subsurface (hyporheic) components of streamflow creates an interconnected (anastomosed) system of channels, wetlands, ponds, and lakes. River-wetland corridors occur where the valley floor is sufficiently wide to accommodate a laterally unconfined river planform that may feature morphologically complex, multi-threaded channels with vegetated bars, islands, and floodplains. River-wetland corridors can develop anywhere there is valley expansion along a drainage network, from the headwaters to estuaries or deltas, and they are found across all latitudes and within all biomes and hydroclimates. River-wetland corridors may be longitudinally continuous but are commonly interspersed with single-thread reaches in narrower portions of the valley. The development and persistence of river-wetland corridors is driven by combinations of geologic, biotic, and geomorphic processes that create a river environment that is diverse, heterogeneous, patchy, and dynamically stable, and within which patterns of flow, sediment features, and habitats shift continually. Hence, we describe these polydimensional river corridors as a ‘kaleidoscope rivers.’ Historically, river-wetland corridors were pervasive in wide, alluvial valley reaches, but their presence has been so diminished worldwide due to a diverse range of anthropogenic activities and impacts that the general public and even most river managers are unaware of their former pervasiveness. Here, we define river-wetland corridors as a river type; review paleoenvironmental and historical records to establish their past ubiquity; describe the geologic, biotic, and geomorphic processes responsible for their formation and persistence; and provide examples of river-wetland corridor remnants that still survive. We close by highlighting the significance of the diverse river functions supported by river-wetland corridors, the consequences of diminution and neglect of this river type, and the implications for river restoration.